Integrated Proteome and Cytokine Profiles Reveal Ceruloplasmin Eliciting Liver Allograft Tolerance via Antioxidant Cascades - Wang, Pei-Wen; Wu, Tung-Ho; Pan, Tai-Long; Chen, Mu-Hong; Goto, Shigeru; Chen, Chao-Long (Frontiers in Immunology, 2018)
Acute rejection (AR) and spontaneous tolerance may occur after allograft orthotopic liver transplants (OLT) performed in certain combinations of donor and recipient rat strains, yet the underlying molecular cascades involved in these conditions remain poorly understood. Comprehensive analysis with proteomic tools revealed that ceruloplasmin was highly expressed during the tolerant period on day 63 post-OLT (POD 63) compared to the rejected samples on POD 14. Meanwhile, cytokine expression profiles implied that the inflammation was significantly stimulated in the AR subjects. Again, protein carbonylation was dramatically upregulated in the rejected subject within the tolerant group. Knockdown of ceruloplasmin would elicit more severe ROS damage, leading to cell death in the presence of H2O2, which induced Nrf2 expression and the recovery of ceruloplasmin to mediate spontaneous tolerance. In summary, ceruloplasmin may contribute to amending the oxidative stress that eventually causes cell apoptosis and to maintaining the survival of hepatocytes in a drug-free tolerance OLT model.